Indications and long-term results of enteral feeding in infancy and childhood - Alsafadi, Danyah Mahmoud; Alzahrani, Gaida Sharaf; Alhayek, Qasem Mohammed; Alghazwi, Hawra Hassan; Alzahrani, Waleed Abdulwahab; Qahtani, Reema Saeed AL; Alfahhad, Afnan Jaber; Hazzazi, Hanan Ahmed; Alyami, Bashayr Dimshaq; Alsakhin, Nasser Ali; Althagafi, Raad Aidh (International Journal Of Community Medicine And Public Health, 2021)
Enteral feeding is more favorable than parenteral one because it can significantly intervene against the colonization of bacteria and preserve gut functions. However, this necessitates the presence of a good-functioning gastrointestinal tract. Young infants, critically ill children, and patients with neurological disabilities are the most probable candidates to perform enteral feeding. In the present literature review, we have discussed the indications and long-term results of enteral feeding in pediatric settings. Our results show that modality is a safe and efficacious modality in these settings with favorable outcomes and fewer adverse events and complications. Many indications were reported for the modality, and in general, children that usually suffer from severe weight deficit, weight faltering, and growth retardation are indicated to receive enteral nutrition. Some contraindications were also reported in the literature, and in general, conditions affecting the function and health status gastrointestinal tract should recommend against conducting approaches of enteral feeding. Different complications were reported, including mechanical, metabolic, infectious, gastrointestinal, and drug-related complications that might lead to worsened prognosis and can significantly impact the long-term outcomes of these patients. Therefore, paying adequate attention should be considered in these cases to prevent the development of these complications, and provide all the necessary procedures to potentially manage the expected adverse events.